Development of collagen functionalized thermally responsive poly(N-isopropylacrylamide) electrospun nanofibers scaffold potentially as a 3D cell culture platform for rat amniotic fluid stem cells - Yong, Hsin Nam Ernest (2023)
2D surfaces such as tissue culture polystyrene dish used in conventional cell culture have limited surface area for cell growth. During harvest, mechanical scraping or trypsin are used to remove confluent cells from their growing surface, which can be harmful to cells and reduce cell yield. Therefore, there is a need for an improved cell growth surface with increased surface area and an alternative non-invasive cell harvesting mechanism. To this end, a potential three-dimensional (3D) cell culture platform was developed with nanofibers of poly(N-isopropylacrylamide) (PNIPAm) as the main structural framework, fabricated via the electrospinning technique. Collagen type I extracted from fish scales of Tilapia fish was used to functionalize PNIPAm nanofibers scaffold via dip-coating to improve cell-scaffold interaction. The developed electrospun PNIPAm nanofibers scaffold exhibits a morphology that highly mimics the native extracellular matrix (ECM) in terms of fiber diameter, measuring 436.35 ± 187.04 nm. Pore size and porosity were computed as 1.24 ± 1.27 nm and 63.6 %, respectively. Collagen functionalized PNIPAm nanofibers scaffolds show significant improvement in cell viability of rat amniotic fluid stem cells (R3- AFSC) with increasing collagen content, with 50, 70 and 180 % cell viability on neat electrospun PNIPAm, PNIPAm dip-coated in 0.1 and 0.5 % (w/w) collagen solution, respectively. On the other hand, increased collagen content reduces the capability of PNIPAm nanofibers scaffold to spontaneously release R3-AFSC upon cooling from cell culture conditions (37 °C and 5 % CO2) to 25 °C (room temperature), with 51, 48 and 43 % of R3-AFSC released from neat electrospun PNIPAm, PNIPAm dip-coated in 0.1 and 0.5 % (w/w) collagen solution, respectively.